Functionalization of graphene: does the organic chemistry matter? - Kasprzak, Artur; Zuchowska, Agnieszka; Poplawska, Magdalena (Beilstein Journal of Organic Chemistry, 2018)
Reactions applying amidation- or esterification-type processes and diazonium salts chemistry constitute the most commonly applied synthetic approaches for the modification of graphene-family materials. This work presents a critical assessment of the amidation and esterification methodologies reported in the recent literature, as well as a discussion of the reactions that apply diazonium salts. Common misunderstandings from the reported covalent functionalization methods are discussed, and a direct link between the reaction mechanisms and the basic principles of organic chemistry is taken into special consideration.
Keywords: characterization; functionalization; graphene; modification; synthesis design